2018
DOI: 10.1002/admi.201801686
|View full text |Cite
|
Sign up to set email alerts
|

Porous Halide Perovskite–Polymer Nanocomposites for Explosive Detection with a High Sensitivity

Abstract: a field-based environment, is critical for homeland security and public safety.In practice, trained canines and spectroscopic techniques have both been used to detect explosive chemicals. However, trained canines are expensive. They can also be fatigued and are not suitable for continuous monitoring. [15] Ion mobility spectrometry has been one of the most used commercial spectroscopic tools to detect explosive chemi cals. [16] It has a high sensitivity ranging from picograms to nanograms. [16] However, due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The exact sensing mechanism behind PL quenching is still controversial: some authors propose a charge transfer mechanism between the PVK NCs and the analyte, and other authors propose trap-state generation in PVK NCs. 38,39…”
Section: Introductionmentioning
confidence: 99%
“…The exact sensing mechanism behind PL quenching is still controversial: some authors propose a charge transfer mechanism between the PVK NCs and the analyte, and other authors propose trap-state generation in PVK NCs. 38,39…”
Section: Introductionmentioning
confidence: 99%
“…To understand the quenching mechanism against nitrophenol exposure, femtosecond transient absorption spectroscopy was performed for the CH 3 NH 3 PbBr 3 thin films with and without TNT exposure. [30] The ground state bleaching and excited state absorption of the CH 3 NH 3 PbBr 3 have shown fast decay at 540 nm within first picosecond and all other signals have shown decay between 1 ps and 6 ns. [31] Among these decay processes, the fast decay was attributed to the cooling of hot carriers, whereas, the delayed processes was the decay of exciton or carriers.…”
Section: Mechanism For Fluorescence Quenching Of Mhp-based Sensorsmentioning
confidence: 92%
“…Shan et al [30] reported the trinitrotoluene (TNT), 1,3,5-trinitroperhydro-1,3,5-triazine (RDX), and trinitroglycerin (TNG) explosives detection by using porous CH 3 NH 3 PbBr 3 -PVDF nanocompsite that is stable in water/isopropanol medium and showed no degradation on expoure to the water contents. The nanocomposite showed 4% PL quenching upon addition of 2 ng of TNT solution.…”
Section: Nitrophenol Sensingmentioning
confidence: 99%
“…Reproduced with permission. [ 144 ] Copyright 2018, Wiley‐VCH. h) Schematic of the solar‐powered tactile sensor.…”
Section: Other Sensing or Detecting Applicationsmentioning
confidence: 99%
“…Hao et al embedded MAPbBr 3 nanocrystals in a poly(vinylidene fluoride) (PVDF) polymer matrix via the freeze‐drying process, obtaining a porous nanocomposite that showed strong fluorescence quenching when exposed to various explosive compounds such as, 2,4,6‐trinitrotoluene (TNT), 1,3,5‐trinitroperhydro‐1,3,5‐triazine (RDX), and trinitroglycerin (TNG), with a high sensitivity of a few nanograms (Figure 15g). [ 144 ] The high porosity increased the specific surface area, thus enhancing the absorption and diffusion process of explosive chemicals toward the perovskite nanocrystals. Meanwhile, the PVDF polymer matrix prevented the penetration of water and alcohol molecules into the composites due to the hydrophobicity.…”
Section: Other Sensing or Detecting Applicationsmentioning
confidence: 99%